Perilaku Sarapan Pada Anak Sekolah - Anas Tamsuri; Aris Dwi Cahyono; Suryono Suryono (SEHATI: Jurnal Kesehatan, 2025)
Breakfast is one of the important habits that affect the physical and cognitive health of children, especially for those who attend school. A healthy and nutritious breakfast can improve academic performance and support optimal growth and development of children. The purpose of this study was to obtain an overview of the breakfast behavior of school-age children and the factors that cause it. The research method used was descriptive quantitative. The population of the study was 340 high school students in grade XI at a school in Kediri Regency. The research sample was 154 respondents. Data collection activities were carried out The research data was collected using a questionnaire, then processed descriptively in the form of a diagram. The analysis was carried out descriptively. From the results of data processing, less than half of the respondents (42.86%) had breakfast regularly every day, and more than a quarter of respondents (27.92%) rarely/never had breakfast. Respondents who did not have breakfast regularly because they were not used to having breakfast or had digestive problems if they had breakfast (34.48%), followed by time constraints (in a hurry and afraid of being late) as much as 31.03%, and there were 25.28% because parents did not prepare food for breakfast. Based on the results, it is suggested that families facilitate children to manage their time so that children have enough time to have breakfast